2020
DOI: 10.3892/ijmm.2020.4534
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA let‑7e is decreased in knee osteoarthritis, accompanied by elevated apoptosis and reduced autophagy

Abstract: Knee osteoarthritis (KOA) is a major cause of leg disability in the elderly population. Recently, the expression levels of circulating microRNA (miRNA) let-7e have been reported to be significantly reduced in KOA. The aims of the present study were to assess the feasibility of let-7e as a serum marker for detecting KOA and to explore the underlying mechanisms of its involvement. Based on previous studies and bioinformatics analysis, let-7e may regulate apoptosis and autophagy of articular chondrocytes. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 49 publications
(57 reference statements)
0
34
1
Order By: Relevance
“…Members of the let-7 family have often been described in studies involving OA; a large population-based study identified serum let-7e as a promising candidate to predict OA risk, independent of age, sex and body mass index [45]. A recent investigation supported this claim, providing further evidence of decreased expression of let-7e in serum of patients affected with knee OA [46]. The exact roles of miRNAs of the let-7 family remain unclear, but the evidence for their use as biomarkers for OA is growing.…”
Section: Discussionmentioning
confidence: 94%
“…Members of the let-7 family have often been described in studies involving OA; a large population-based study identified serum let-7e as a promising candidate to predict OA risk, independent of age, sex and body mass index [45]. A recent investigation supported this claim, providing further evidence of decreased expression of let-7e in serum of patients affected with knee OA [46]. The exact roles of miRNAs of the let-7 family remain unclear, but the evidence for their use as biomarkers for OA is growing.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, the inhibition of chondrocytes apoptosis by autophagy activation has attracted much attention (Shapiro et al, 2014). Recent studies have shown that the level of autophagy in OA cartilage is reduced (Feng et al, 2020), and autophagy can protect chondrocytes from degradation (Caramés et al, 2012). With the progress of OA, mammalian target of rapamycin (mTOR), the main negative regulator of autophagy, is up-regulated and mediates the inhibition of autophagy signal transduction in articular cartilage, and the protective effect of autophagy on cartilage decreases, eventually promoting cartilage degeneration (Vasheghani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an essential cellular and molecular mechanism that is important for maintaining cellular homeostasis [ 39 ], and it has been reported that autophagy is reduced in the cartilage of OA patients [ 40 ]. Recently Wang and colleagues reported the protective effects of metformin against osteoarthritis through the activation of autophagy [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%